The Lion and the Lily: Map and Atlas Production in Early Modern England and France. - Petto, Christine Marie (2011)
Dr. Petto completed chapters 2 and 3 and a book proposal for her second manuscript, The lion and the lily: map and atlas production in early modern England and France. Chapter 2 describes local mapping and hydrographic charting initiatives in the 17th and 18th century; chapter 3 focuses on scientific cartography and the efforts of both crowns to map colonial interests in the Americas and Asia. She obtained book contract with Lexington Books, with release date of July 2013.
Keywords: dept.his; faculty_collection; sabbatical_report

Friday Night Fighter: "Indio" Ortega and the Golden Age of Televised Boxing. - Rondinone, Troy (Spring ; History., 2011)
Keywords: dept.his; faculty_collection; sabbatical_report

A History of Smallpox and Preventive Treatments for It in the Lands Bordering the South China Sea - Thompson, C. Michele (2011)
Keywords: dept.his; faculty_collection; sabbatical_report

Religion and Identity in Russia and the Soviet Union A Festschrift for Paul Bushkovitch - Chrissidis, Nikolaos A. (Slavica Publishers, Slavica, 2011)
Keywords: Bushkovitch, Paul; Nationalism; History; Christianity and politics; History; Identity (Psychology); History; Nationalism; History; Soviet Union; Politics and government; Politics and government; Russia; Religious aspects; Russia; Russkai͡a pravoslavnai͡a t͡serkovʹ; National characteristics, Russian; Soviet Union; dept.his; faculty_collection

We Will Be Satisfied with Nothing Less: The African American Struggle for Equal Rights in the North During Reconstruction - Davis, Hugh (Cornell University Press, 2011)
Historians have focused almost entirely on the attempt by southern African Americans to attain equal rights during Reconstruction. However, the northern states also witnessed a significant period of struggle during these years. Northern blacks vigorously protested laws establishing inequality in education, public accommodations, and political life and challenged the Republican Party to live up to its stated ideals. In "We Will Be Satisfied With Nothing Less," Hugh Davis concentrates on the two issues that African Americans in the North considered most essential: black male suffrage rights and equal access to the public schools. Davis connects the local and the national; he joins the specifics of campaigns in places such as Cincinnati, Detroit, and San Francisco with the work of the National Equal Rights League and its successor, the National Executive Committee of Colored Persons. The narrative moves forward from their launching of the equal rights movement in 1864 to the "end" of Reconstruction in the North two decades later. The struggle to gain male suffrage rights was the centerpiece of the movement's agenda in the 1860s, while the school issue remained a major objective throughout the period. Following the ratification of the Fifteenth Amendment in 1870, northern blacks devoted considerable attention to assessing their place within the Republican Party and determining how they could most effectively employ the franchise to protect the rights of all citizens.-- Book jacket.
Keywords: 1863-1877; African Americans; 19th century; Equality before the law; 19th century; Reconstruction (U.S. history, 1865-1877); African Americans; Civil rights; History; United States; dept.his; faculty_collection

Sex, drink, and drugs: Tobacco in seventeenth-century Russia - Chrissidis, N.A. (Tobacco in Russian History and Culture: From the Seventeenth Century to the Present, 2011)
Keywords: dept.his

Manufacturing Mohism in the Mencius - Radice, T. (Asian Philosophy, 2011)
The Mencius contains several negative remarks about the Mohists and their doctrine of 'universal love' (jian'ai). However, little attention has been paid to whether Mencius' descriptions of Mohism were accurate. Fortunately, there is a surviving record of the beliefs of Mozi in the text that bears his name. In this essay, I analyze this text and descriptions of Mohism from other early Chinese texts, and compare them to the criticisms of Mohism in the Mencius. Ultimately, I show that the image of the Mohists as ones who promoted a doctrine that contradicted filial piety was inaccurate, and obscured the complexities of filial piety in the Warring States period. © 2011 Taylor and Francis.
Keywords: dept.his; peer-reviewed

Teaching the Great War through Peace - Shortell, Catherine K.; Paddock, Troy R. E. (The History Teacher, 2011)
Keywords: dept.his; ⛔ No DOI found

Red power rising: the national indian youth council and the origins of native activism - Amerman, Steve (The Journal of American History, 2011)
Keywords: dept.his; peer-reviewed

Education beyond the mesas: hopi students at sherman institute, 1902–1929 - Amerman, Steve (Western Historical Quarterly, 2011)
Keywords: dept.his

Muhammad and the believers: at the origins of islam. by fred m. donner - Judd, Steven (Journal of the American Academy of Religion, 2011)
Keywords: dept.his

Muslim Persecution of Heretics during the Marwānid Period (64–132/684–750) - Judd, Steven (Al-Masaq: Journal of the Medieval Mediterranean, 2011)
This article traces the emergence of a systematic approach to combating heresy during the Umayyad period. It argues that the Umayyads sought to silence religious dissent by labelling it as heresy and that the doctrinal boundaries of orthodoxy narrowed as the Umayyad period progressed. The article also asserts that Umayyad efforts to impose their vision of orthodoxy were an important precedent for the mihna under the Abbasids. © 2011 Society for the Medieval Mediterranean.
Keywords: Abd al-Malik; Ghaylan al-Dimashqi; Heretic; Hisham; Islam - heresy; Islamic scholar; Mabad al-Juhani; Qadariyya; Theological movement; Ummayad caliph; Ummayad caliphate; dept.his

Rosemont, jr., henry, and roger t. ames, the chinese classic of family reverence: A philosophical translation of the xiaojing - Radice, Thomas (Dao-a Journal of Comparative Philosophy, 2011)
Keywords: dept.his; peer-reviewed